Social media use, corporate entrepreneurship and organizational resilience: A recipe for SMEs success in a post-Covid scenario - Martín-Rojas, Rodrigo; Garrido-Moreno, Aurora; García-Morales, Víctor J. (Technological forecasting & social change, 2023)
The strategic use of social media tools facilitates firms' entrepreneurial capabilities, enabling them to become more innovative, increasing their proactivity, and helping them to renew themselves internally. In today's turbulent landscape, organizational resilience has emerged as a key variable for responding to external challenges and facing uncertainty. In this context, our study aims to analyze the role of social media use as an antecedent of corporate entrepreneurship and firm performance in Spanish SMEs, while also examining the mediating role of organizational resilience in this process. Analyzing data from a sample of 259 firms, we tested our proposed hypotheses using structural equation modeling. The results confirm that use of social media tools positively impacts the entrepreneurial capabilities of the SMEs examined. The findings also stress the strategic relevance of organizational resilience, which exerts a perfect mediating impact on firm performance. These findings have significant implications for managers, as they show the path managers must take to benefit from social media use, become more entrepreneurial and resilient, and achieve business success in these turbulent times. •Social media fosters firm internal processes like corporate entrepreneurship (CE).•Social media use enhances SMEs entrepreneurial capabilities and performance.•Organizational resilience perfectly mediates the impact of CE on SMEs performance.•Organizational resilience is crucial for firms to grow in the current environment.